2018
DOI: 10.3758/s13414-018-1586-8
|View full text |Cite|
|
Sign up to set email alerts
|

Listening back in time: Does attention to memory facilitate word-in-noise identification?

Abstract: The ephemeral nature of spoken words creates a challenge for oral communications where incoming speech sounds must be processed in relation to representations of just-perceived sounds stored in short-term memory. This can be particularly taxing in noisy environments where perception of speech is often impaired or initially incorrect. Usage of prior contextual information (e.g., a semantically related word) has been shown to improve speech in noise identification. In three experiments, we demonstrate a comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…This suggested that the retrospective semantic link between the target and retro-cue allowed to disambiguate the noisy representation of the target. An important difference between these findings and the current study is that, in Chan and Alain (2019), the target word always received full attention: there was a single auditory stream, which onset was always preceded by a 3 s visual countdown, so that there was no spatial nor temporal uncertainty. The target was therefore presumably always detected, but its identity could be ambiguous.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This suggested that the retrospective semantic link between the target and retro-cue allowed to disambiguate the noisy representation of the target. An important difference between these findings and the current study is that, in Chan and Alain (2019), the target word always received full attention: there was a single auditory stream, which onset was always preceded by a 3 s visual countdown, so that there was no spatial nor temporal uncertainty. The target was therefore presumably always detected, but its identity could be ambiguous.…”
Section: Discussioncontrasting
confidence: 78%
“…While the influence of retrospective cueing has been largely investigated in vision, to date only a few studies have explored this topic in audition (Backer & Alain, 2012; Chan & Alain, 2019, 2021; Lim et al, 2015). Some of these studies showed an auditory equivalent of the classical Sperling effect, using several auditory sources at various locations, as described in the introductory part (Backer & Alain, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, a gap before the masker most often eliminated the illusory texture percept (two-tailed paired t -test comparing the proportion of continuous responses in the contiguous and gap-before-noise conditions, t(9) = 4.98, p < 0.001), but illusory texture was heard to fade in more often than when gaps were both before and after the noise (two-tailed paired t -test comparing the proportion of fade-in responses in the gap-before-and-after and gap-before-noise conditions, t(9) = 3.40, p = 0.0078). The latter effect suggests some degree of “retrospective” filling-in 2325 driven by the texture occurring after the noise.…”
Section: Resultsmentioning
confidence: 99%
“…Each list used in the present study consisted of 10 randomly selected logatomes. The choice to use this type of speech audiometry aims to minimize the mnemonic effort of the subjects: the speech intelligibility tends to differ between logatomes and words because they are not supported by semantic and long-term memory (Pisoni, 1996;Chan and Alain, 2018). The average of the intrasubject differences has been estimated between 5 and 20% (in favor of words) of recognized signals, even in the best hearing conditions.…”
Section: Audiological Assessmentmentioning
confidence: 99%